2011
DOI: 10.1002/jmv.22249
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus genotyping in Greece: Unexpected high prevalence of genotype 5a in a Greek island

Abstract: Hepatitis C virus (HCV) genotype 5 (G5) is a rare genotype reported mainly in South Africa. However, increasing data suggest the sporadic presence of this genotype in different European countries. To assess the epidemiology of HCV-G5 in Greece, genotyping was performed in 973 consecutive patients infected with HCV, referred to 7 hepatology centers throughout Greece, from January 2005 to December 2009. Genotype 5a (19 patients, 1.9%) was the fifth most prevalent genotype after genotype 1 (408 patients, 41.9%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…The source of infection is unknown but parenteral iatrogenic routes of transmission have contributed to infection [17]. …”
Section: Discussionmentioning
confidence: 99%
“…The source of infection is unknown but parenteral iatrogenic routes of transmission have contributed to infection [17]. …”
Section: Discussionmentioning
confidence: 99%
“…While in Greece HCV-5 has a prevalence of 1.9% (19/973), in Rhodes 13% (16/122) were found; 82% (13/16) of the patients infected with HCV-5a in Rhodes were females and the average age was 62 ± 6 years [19]. The iatrogenic route of genotype 5a, that is usually prevalent in Southern Africa, could fairly be linked to dental or surgical interventions.…”
Section: Hepatitis C Virus (Hcv) Transmission By Injection Of Drugs Tmentioning
confidence: 99%
“…In Congo-Kinshasa a cohort of 299 males was investigated, 13.7% (41/299) of the patients were seropositive and 3.7% (11/299) viraemic; age correlation revealed that 13.7% (10/73) of those older 50, and 0.5% (1/211) younger 50 years were viraemic. The HCV genotypes were 4c, 4k, 4l and 4r and thus it was concluded that different separate HCV epidemics by parenteral injections, iatrogenic or another unidentified routes in the mid-twentieth century caused this epidemic [19, 21]. In a more recent study of 839 participants 26% (217/839) were anti-HCV positive and genotype distribution of 4k and 4r was detected in hospital A, with a risk factor of intramuscular and intravenous injection therapy for tuberculosis, while genotype 4k in hospital B in Kinshasa was associated with injection of anti-malarias.…”
Section: Hepatitis C Virus (Hcv) Transmission By Injection Of Drugs Tmentioning
confidence: 99%
“…2 HCV genotype 5 (HCV-5) is mainly restricted to South Africa, where it accounts for up to 40% of the overall HCV. 12,13 We recently reported a cluster of HCV-5-infected patients in southeast Greece and described their clinical and epidemiological characteristics. [5][6][7][8][9][10][11] In Greece, prevalence of HCV-5 has been estimated to be 0.4% to 1.9%.…”
mentioning
confidence: 99%
“…3,4 However, sporadic presence of HCV-5 has been reported in other parts of the world including France, Belgium, Canada, Syria, Spain, Germany, and Brazil. 12 Briefly, patients infected with HCV-5 were mostly females of advanced age showing high levels of viremia and advanced hepatic fibrosis. 12,13 We recently reported a cluster of HCV-5-infected patients in southeast Greece and described their clinical and epidemiological characteristics.…”
mentioning
confidence: 99%